Konseling Keluarga dalam Perspektif Budaya Indonesia - Hidayani Syam; Akifa Aliya; Adil Putalo; Alwi Usman Matondang (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
Family counseling is a strategic approach to helping family members overcome various issues that disrupt family harmony and functionality. In the Indonesian context, family counseling cannot be separated from the influence of distinctive local cultural values such as kinship, mutual cooperation (gotong royong), respect for elders, and the strong presence of religious and customary norms. Indonesian culture, which is predominantly collectivist and hierarchical, places the family as the central social institution that shapes individual identity and behavior. Therefore, it is essential for counselors to understand the diverse family structures present in Indonesia, ranging from patriarchal and matrilineal systems (such as in Minangkabau) to more egalitarian modern families. Culturally-based family counseling in Indonesia not only focuses on resolving interpersonal conflicts within the family but also emphasizes the importance of maintaining social harmony and protecting the family’s reputation in the community. In Indonesian society, conflict resolution is often carried out through deliberation (musyawarah) and involves third parties such as community elders, religious leaders, or respected senior family members. This highlights the need for family counselors in Indonesia to possess intercultural competence and a deep understanding of prevailing social norms. Moreover, religiosity plays a significant role in shaping values, attitudes, and decision-making within families. Counseling approaches that neglect the spiritual and cultural dimensions are often perceived as irrelevant or ineffective. Thus, integrating Western psychological theories with local values is crucial for family counseling to be both effective and contextually appropriate. This article explores the importance of culturally grounded family counseling in Indonesia by emphasizing key principles such as local wisdom, togetherness, deliberation, and harmony as the foundation for intervention strategies. By understanding the complexities of Indonesia’s pluralistic culture, family counseling can become a powerful tool to rebuild healthy, sustainable relationships and support the development of a more emotionally and socially harmonious society.